Assessment Professional Functions in Land Procurement of National Strategic Projects in Realizing Legal Certainty Principle - Henricus Judi Adrianto; Joni Emirzon; Aartje Terhupeiory; Bernard Nainggolan (International Journal of Social Service and Research, 2023)
This study also aims to analyze the application and completion of consignment in land acquisition for general interests in terms of the perspective of judicial decisions. The data collection procedures used in this study were questionnaires, observations, interviews, documentation. Data analysis techniques in this study use qualitative analysis that is inductive, which is an analysis based on the data obtained, then a certain relationship pattern is developed. From various studies, this research concludes that the trigger for conflicts related to land acquisition often occurs because the value of compensation / compensation given to affected communities is not given properly and fairly, lacks transparency and harms the community. In addition to problems related to injustice, it is stated that some land acquisitions carried out in Indonesia have not fully involved community participation, lack of counseling/socialization processes and meaningful public consultations on land acquisition plans carried out by parties who need land to the community, have not compiled land acquisition planning documents that are studied in depth in accordance with the environmental, socio-economic conditions of the community  and the lack of involvement of parties/agencies that have authority related to land acquisition since the initial planning process.